MALARIA, POVERTY AND CHILD HEALTH IN NIGERIA: ANY NEXUS? - AKINTUNDE, Temitope; ARIBATISE, Adekunle; AKANBI, Bosede (Journal of Social Sciences)
Infant mortality rates remain high in many African countries, despite global lowering trends. These high rates are alarming, therefore, this study attempt to examine the effect of malaria and poverty on infant mortality a proxy for child health in Nigeria using a data for the period 1990-2021. Auto-regressive distributed lag model (ARDL) was used as the estimation technique. The study's findings showed that both in the short and long run, poverty rate has a negative non-significant effect on infant mortality while malaria has a positive and significant effect on infant mortality. Government expenditure on health both in the short run and long run is positive and nonsignificant on child health. The current values of primary school enrolment (PSE) and number of physician (NOP) have a negative (-0.014 and -0.0002) non-significant effect on infant mortality in the short, and also negative (-0.501 and -1.654) but significant in the long run. The study recommends that policies that will improve child health and promote poverty reduction should be put in place and well implemented in Nigeria. Also, the government should take measures that will eradicate malaria in Nigeria.